IoT-Based Prototype System for Automated Measurement of Human Height, Body Weight, and Temperature Using Sensors - Christian P. Colombini; Frencis M. Sarimole (International Journal Software Engineering and Computer Science (IJSECS), 2025)
This study presents the development of an IoT-based prototype for automatic measurement of body height, weight, and temperature using Arduino Uno microcontroller. The research responds to operational challenges observed at Puskesmas Cengkareng Timur, where conventional manual measurement tools contribute to process inefficiencies and frequent data recording errors during patient examinations. The prototype integrates three sensor components: HC-SR04 ultrasonic sensor for height measurement, Load Cell with HX711 amplifier module for weight detection, and MLX90614 infrared sensor for contactless temperature monitoring. Sensor outputs are processed through Arduino Uno and displayed via I2C LCD interface. Performance evaluation through laboratory calibration and field trials indicates measurement accuracy within 0.15% error margin across all parameters. Implementation of this device at the health center demonstrates potential for improving service delivery efficiency and reducing patient queue duration during preliminary health screening